Pengaruh Pendidikan Kesehatan Terhadap Perubahan Pengetahuan, Sikap dan Perilaku Tentang Kebiasaan Berperilaku Hidup Bersih dan Sehat Siswa SDN 1 Mandong - Pratama, Ryan Kendi Okta; , Arif Widodo, A.Kep., M.Kes; , Dewi Listyorini, S.Kep., Ns (2013)
School age children are past the age of children who are very different from adults. Obtained within this period many health issues that determine the quality of the child's future . At the elementary school students faced health problems associated with living clean and healthy behavior that have not been implemented well . From the observations and interviews of 7 students , 5 students in the habit of littering them is not in place , there are often students do not participate in sports at school , students snack foods outside of school , many students did not wash their hands before taking food . The research objective was to determine the effect of health education on changes in knowledge , attitudes and behaviors about clean living habits and unhealthy behavior SDN 1 Mandong students . This type of research is a quantitative research design one group pre test and post test design . Sampling technique with a total sampling with a sample of 52 respondents . Research instrument in the form of knowledge and attitude questionnaires and observation sheets for behavior . Research data obtained by giving the test twice before and after the health education given health education . Analysis of research data using paired t test and Wilcoxon rank test test . Results reveal the knowledge , attitudes and behaviors of students increased after receiving health education . Knowledge of data analysis results obtained by paired sample test = 9.543 p = 0.001 , analysis of data obtained attitude test for paired samples = 11.122 with p = 0.001 and behavior change with the value of Wilcoxon rank test = 3.411 with p = 0.001 . Studies conclusion was no effect of health education on changes in knowledge , attitudes and behaviors of good hygiene practices and healthy school SDN 1 Mandong .